Elements of the Control Process for Quality Management in Companies in the Petrochemical Sector - Carlos Alberto Severiche Sierra; Rocío Gutiérrez Echeverría; Jorvich García Correa; Geraldine Morales Simancas; Orleydis Batista Ayola (Revista Científica Profundidad Construyendo Futuro)
The elements of the control process for strengthening quality management in petrochemical companies were identified. Work with a quantitative approach, explanatory type, is considered field with non-experimental, transactional design. The intentional sample was 16 managers from different petrochemical companies who were involved with the organizational processes of administrative areas. The observation technique through a survey was used, the applied questionnaire has items with multiple response options for five (5) alternatives, as follows: Always; Almost Always; Sometimes, Almost Never, and Never. The results reveal that the advantages of digital transformation are almost always taken advantage of because customer experience, efficiency, data are analyzed, and there is capture, conversion and loyalty, that the advantages of digital transformation are taken advantage of, which is why management is indifferent to its implementation. These findings are aligned with the recommendations of the literature on the importance of the constant application of quality tools and the integration of digital technologies.